PENGARUH PENYULUHAN KESELAMATAN DAN KESEHATAN KERJA TERHADAP PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI - Asyera Surbakti; Mapeaty Nyorong; Nur Aini (Jurnal Kesehatan dan Kedokteran, 2023)
The development of occupational safety and health sciences in the work environment can be seen with the development of advanced science and technology. This research is quasi-experimental research (quasi-experimental). This study used a one group pretest and pottest design. The population in this study were workers in the production division a total of 50 workers. The sampling technique (sampling technique) in this study is total sampling. The measuring instrument in this study used univariate and bivariate, non-parametric data distribution using the Wilcoxon test. The results of the Wilcoxon statistical test on both knowledge and attitude obtained a P-value of 0.000. That is, at 5% alpha there is a significant difference in the median score between before and after counseling. While in the aspect of action, there was an increase in the number of PPE users between before and after counseling. Because the results of Asymp.Sig knowledge, attitudes and actions are smaller than 0.05, it means that H0 is rejected, so there is an effect of occupational health and safety (K3) education on the behavior of using PPE. The conclusion is that there is an influence of Occupational Safety and Health (K3) Counseling on the Behavior of Using Personal Protective Equipment at PT. Wijaya Karya Beton Tbk Medan in 2021. Suggestions provide strict sanctions against workers who do not use personal protective equipment while working.